VASA mRNA (DDX4) detection is more specific than immunohistochemistry using poly- or monoclonal antibodies for germ cells in the male urogenital tract. Issue 30 (July 2017) - Boellaard, Willem P.A.; Stoop, Hans; Gillis, Ad J.M.; Oosterhuis, J. Wolter.; Looijenga, Leendert H.J.
Abstract : Abstract: VASA, also known as DDX4, is reported to be specifically expressed in cells belonging to the germ cell lineage, both in males and females. Therefore, it could be an informative protein biomarker to be applied on semen to differentiate between obstructive and nonobstructive azoospermia (OA and NOA, respectively). In addition, it could be of value to predict sperm retrieval based on testicular sperm extraction. Immunocytochemistry of proven OA semen using both polyclonal and monoclonal antibodies against VASA showed positive staining of both cells and cell sized particles. This is spite of being the absolute negative controls, completely lacking germ lineage derived cells and material. In order to identify the source of the VASA-positive material, a detailed screen of different anatomical parts of the whole male urogenital tract was performed of multiple cases using immunohistochemistry. The polyclonal antibody stained, besides the expected germ cells in the testis, epithelium of the bladder and the seminal vesicles. The monoclonal antibody only stained the latter. To investigate whether the immunohistochemical staining is associated with the presence of the corresponding VASA mRNA, samples of seminal vesicles, bladder, testis, and semen (with and without germ cells) were investigated using the specific quantitative reverse transcription-polymerase chain reaction (qRT-PCR) on 42 samples. A positive result was detected in testis and semen containing germ cells (n = 10 and 8), being negative in semen without germ cells (n = 11), bladder (n = 3), and seminal vesicles (n = 10). Two commercially available VASA antibodies (mono- and polyclonal) are not specific. In contrast, VASA-mRNA evaluation, using qRT-PCR, is specific for the presence of germ cells, therefore, is an interesting molecular biomarker for germ cell detection in semen. Abstract : Supplemental Digital Content is available in the text